SOSIALISASI MENGENAL INVESTASI DI BURSA EFEK: PENINGKATAN PEMAHAMAN TENTANG PERAN PERMODALAN DALAM PEREKONOMIAN - Laode Muhammad Hasrul Adan; Waode Adriani; Nur Azmi Apriyanti; Hasbiallah Hasbiallah (Jurnal Pengabdian Masyarakat Sabangka, 2026)
Low levels of financial literacy among rural communities, particularly regarding stock market investment, remain a significant challenge to local economic development. Limited understanding of capital market instruments restricts rural residents’ participation in formal financial systems, thereby widening the financial access gap between urban and rural areas. This community service program aims to enhance financial literacy and capital market inclusion through a participatory approach grounded in andragogical principles. The activities included needs assessment, development of contextualized capital market education materials, and the implementation of seminars, workshops, and simulations of stock and bond trading. Educational content was tailored to local economic conditions and delivered using relevant case studies to encourage active participation and practical application. The results indicate an improvement in participants’ basic knowledge of the capital market, a more positive attitude toward formal investment, and enhanced practical skills in opening securities accounts and selecting investment products based on individual risk profiles. This program contributes to increasing capital market inclusion and strengthening the long-term local capital base in rural communities.